Structural racism in healthcare and research: A community-led model of curriculum development and implementation. Issue 1 (9th November 2023) - Terrance, Traci C.; Sugarwala, Laura; McIntosh, Scott; Bisbee-Burrows, Mary; Castillejo, Lucia; Evans, Alicia; Reed, Katie; Rogers, Karen; Cullen, John P.
Abstract: Structural racism in the USA has roots that extend deep into healthcare and medical research, and it remains a key driver of illness and early death for Black, Indigenous, People of Color (BIPOC). Furthermore, the persistence of racism within academic medicine compels an interrogation of education and research within this context. In the spirit of this interrogation, this article highlights a unique model of community-engaged education that integrates cultural humility. As an individual and institutional stance, cultural humility denotes lifelong learning and self-critique, the mitigation of power imbalances, and accountability. The integration of cultural humility emphasizes that when space is created for BIPOC communities to lead the way, education regarding healthcare and research can be effectively reimagined. Demonstrating this effectiveness, six community partners led the development and implementation of a five-module Structural Racism in Healthcare and Research course. Using a cohort model approach, the pilot course enrolled 12 community members and 12 researchers. The curriculum covered topics such as history of racism in healthcare and research, and introduced participants to a cultural resilience framework. Evaluation results demonstrated a significant increase in participants' knowledge and ability to identify and take action to address inequities related to racism in healthcare and research.